TI_GERICHTE 14.2012.135 vom 2. August 2012 , Domanda di restituzione in intero. Revoca del fallimento ex art. 174 II LEF - TI Tribunale d'appello (2012)
Domanda di restituzione in intero. Revoca del fallimento ex art. 174 II LEF